2014
DOI: 10.1515/ssr-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

Wii Teach Movement Qualities in Physical Education

Abstract: In Sweden, the PE curriculum states that students are expected to develop a number of abilities, a variety of movement activities and qualities. Interesting to explore is then if exergames (video games that includes physical activity) can be seen as a teaching resource to learn different movement's qualities. With a new teaching tool that has been introduced in education and new policy documents emphasising development of different movement qualities, the purpose of this article is accordingly to investigate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…When students struggle to establish connections to their broader lives, they report a lack of meaningfulness in these physical education and youth sport experiences (Koekoek et al, 2009;Quennerstedt, 2013;Redelius, Quennerstedt, & Öhman, 2015;Smith & Parr, 2007). The use of exergames represents one contemporary way to help students make connections between physical education in schools and physical activity interests outside school and thus enhance meaningful participation for students (Maivorsdotter et al, 2015;Meckbach, Gibbs, Almqvist, & Quennerstedt, 2014).…”
Section: Personally Relevant Learningmentioning
confidence: 99%
“…When students struggle to establish connections to their broader lives, they report a lack of meaningfulness in these physical education and youth sport experiences (Koekoek et al, 2009;Quennerstedt, 2013;Redelius, Quennerstedt, & Öhman, 2015;Smith & Parr, 2007). The use of exergames represents one contemporary way to help students make connections between physical education in schools and physical activity interests outside school and thus enhance meaningful participation for students (Maivorsdotter et al, 2015;Meckbach, Gibbs, Almqvist, & Quennerstedt, 2014).…”
Section: Personally Relevant Learningmentioning
confidence: 99%
“…The study reported in this paper is part of a larger four-year project funded by the Swedish Research Council, which includes a group of researchers taking part in the data collection and analysis of the qualitative data (Meckbach et al, 2014; Öhman et al, 2014; Quennerstedt et al, 2013). In the project, PE lessons in which exergames are used in combination with ‘free choice’ activities organised by the PE teacher are video-recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Nyberg & Meckbach (2015) continue this argument showing students' knowledge in relation to dance exergames. Meckbach, Gibbs, Almqvist & Quennerstedt (2014) show how different movement qualities are offered in the games.…”
Section: Teaching With Artifactsmentioning
confidence: 99%